Energy-Efficient Network Protocols for Domestic IoT Application Design - Gray, Chrispin Alfred; Campbell, Leith; Ayre, Robert; Hinton, Kerry (Journal of Telecommunications and the Digital Economy, 2019)
In the future Internet of Things, many common household devices will have communications interfaces added. The gathering of data from these household IoT-enabled devices will incur an energy cost and, in this paper, we investigate the impact of different communications technologies and protocols on that cost. As a first step towards energy-efficient design, we have measured the power consumption of several popular wireless interfaces – Bluetooth (Classic and Low Energy), ZigBee, Wi-Fi and 433 MHz module (RF433). We then combine these measurements through the example of a simple domestic stock control application and we show how an energy-efficient communications paradigm can be designed in each case. In general, both the communications paradigm and the amount of traffic need to be considered for an energy-efficient design. This is a contribution to design guidelines for energy-efficient communication in the Internet of Things as it expands to encompass all consumer devices.